2021
DOI: 10.1097/wco.0000000000001008
|View full text |Cite
|
Sign up to set email alerts
|

Network dysfunction in pre and postsurgical epilepsy: connectomics as a tool and not a destination

Abstract: Purpose of reviewPatients with focal drug-resistant epilepsy (DRE) sometimes continue to have seizures after surgery. Recently, there is increasing interest in using advanced network analyses (connectomics) to better understand this problem. Connectomics has changed the way researchers and clinicians view DRE, but it must be applied carefully in a hypothesis-driven manner to avoid spurious results. This review will focus on studies published in the last 18 months that have thoughtfully used connectomics to adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The SOZ and PZ power was not significantly altered in the alpha band [8][9][10][11][12] Hz] (Figure 2B). The SOZ and PZ power was elevated compared to baseline in both beta [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and gamma bands , but post-hoc multiple comparisons revealed that the SOZ elevation in power was only significantly different from non-involved regions in the beta band and only from PZs in the gamma band (Figure 2C-D, beta: SOZ single-population t-test p-value=9.00e-3, one-way ANOVA p-value=2.98e-2, post-hoc pairwise t-test comparison SOZ-Non p-value=2.24e-2; gamma: SOZ single-population t-test p-value=6.70e-3, one-way ANOVA p-value=1.11e-2, post-hoc pairwise t-test comparison SOZ-PZ p-value=1.33e-2).…”
Section: Low Frequency Power Is Attenuated In Sozs When the Network I...mentioning
confidence: 86%
See 3 more Smart Citations
“…The SOZ and PZ power was not significantly altered in the alpha band [8][9][10][11][12] Hz] (Figure 2B). The SOZ and PZ power was elevated compared to baseline in both beta [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and gamma bands , but post-hoc multiple comparisons revealed that the SOZ elevation in power was only significantly different from non-involved regions in the beta band and only from PZs in the gamma band (Figure 2C-D, beta: SOZ single-population t-test p-value=9.00e-3, one-way ANOVA p-value=2.98e-2, post-hoc pairwise t-test comparison SOZ-Non p-value=2.24e-2; gamma: SOZ single-population t-test p-value=6.70e-3, one-way ANOVA p-value=1.11e-2, post-hoc pairwise t-test comparison SOZ-PZ p-value=1.33e-2).…”
Section: Low Frequency Power Is Attenuated In Sozs When the Network I...mentioning
confidence: 86%
“…75,[87][88][89][90][91] Overall, when presumably healthy regions were stimulated, the SOZ theta [4-8 Hz] relative band power was markedly decreased from pre-stimulation baseline. Conversely, SOZ beta [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and gamma relative band power increased when healthy regions were stimulated. Increased inward evoked gamma band power in SOZs is in alignment with previous low-frequency stimulation findings.…”
Section: Does Imbalanced Reciprocal Connectivity Indicate Suppression?mentioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, there is growing interest in multimodal image integration pipelines suitably designed for the clinical workflow [34]. The value of connectomics in unveiling network alterations in drug-resistant focal epilepsy was recently underscored [35]. Leveraging deep learning in combination with network neuro-science presents opportunities to identify salient features in high-dimensional imaging datasets [36].…”
Section: Introductionmentioning
confidence: 99%